2006
DOI: 10.1104/pp.106.086306
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals a Critical Role ofCHS7andCHS8Genes for Isoflavonoid Synthesis in Soybean Seeds

Abstract: We have used cDNA microarray analysis to examine changes in gene expression during embryo development in soybean (Glycine max) and to compare gene expression profiles of two soybean cultivars that differ in seed isoflavonoid content. The analysis identified 5,910 genes that were differentially expressed in both soybean cultivars grown at two different locations for two consecutive years in one of the five different stages of embryo development. An ANOVA analysis with P value , 0.05 and , 0.01 indicated that ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 34 publications
4
116
0
1
Order By: Relevance
“…Currently, Medicago, Lotus, and soybean cDNA and oligonucleotide microarrays are available (Endo et al, 2002;Vodkin et al, 2004;Firnhaber et al, 2005). An increasing collection of legume seed transcriptome and proteomic data (Thibaud-Nissen et al, 2003;Firnhaber et al, 2005;Hajduch et al, 2005;Buitink et al, 2006;Dhaubhadel et al, 2007), cDNA library collections, and public EST databases (Journet et al, 2002;Shoemaker et al, 2002;Asamizu et al, 2004;Firnhaber et al, 2005;Ramirez et al, 2005) have helped to provide a global view of gene activity at specific seed developmental stages. Sequences of the Medicago, Lotus, soybean, common bean, and peanut genomes (Broughton et al, 2003;Gepts et al, 2005;Young et al, 2005;Jackson et al, 2006) should provide an invaluable resource for identifying and characterizing genes that play critical roles during seed and embryo development in the near future.…”
Section: Legumes Have Been Used To Study Seed Development For More Thmentioning
confidence: 99%
“…Currently, Medicago, Lotus, and soybean cDNA and oligonucleotide microarrays are available (Endo et al, 2002;Vodkin et al, 2004;Firnhaber et al, 2005). An increasing collection of legume seed transcriptome and proteomic data (Thibaud-Nissen et al, 2003;Firnhaber et al, 2005;Hajduch et al, 2005;Buitink et al, 2006;Dhaubhadel et al, 2007), cDNA library collections, and public EST databases (Journet et al, 2002;Shoemaker et al, 2002;Asamizu et al, 2004;Firnhaber et al, 2005;Ramirez et al, 2005) have helped to provide a global view of gene activity at specific seed developmental stages. Sequences of the Medicago, Lotus, soybean, common bean, and peanut genomes (Broughton et al, 2003;Gepts et al, 2005;Young et al, 2005;Jackson et al, 2006) should provide an invaluable resource for identifying and characterizing genes that play critical roles during seed and embryo development in the near future.…”
Section: Legumes Have Been Used To Study Seed Development For More Thmentioning
confidence: 99%
“…As suggested by earlier reports, the use of methyl jasmonate might activate the respective genes in the phenylpropanoid (PP) pathway (DIXON and PAIVA 1995). The varied expression of IFS genes (IFS1 and IFS2) is responsible for the changes in level of isoflavones in seeds under elicitor treatment (DHAUBHADEL et al 2007, CHENG et al 2008. Also, yeast extract elicited the accumulation of isoflavones via elevated level of L-phenylalanine ammonia lyase and chalcone synthase transcripts in cell suspension of Medicago truncatula (SUZUKI et al 2005) and transcripts of flavanone 2-hydro-xylase, isoflavone 2'-hydroxylase, and isoflavone synthase in Glycyrrhiza echinata cell suspension cultures (NAKAMURA et al 1999).…”
Section: Discussionmentioning
confidence: 90%
“…The similarity of somatic embryos to seeds may thus be lost at the late stages of maturation. However, transcriptome and proteome analyses of developing soybean seeds have indicated that many, but not all, genes involved in the production of seed components, including storage reserves and secondary metabolites, are expressed from an early stage of seed development (Hajduch et al 2005;Dhaubhadel et al 2007). Transcripts of such genes were also detected by microarray analysis of somatic embryos (Thibaud-Nissen et al 2003).…”
Section: Changes In Cellular Organization During Maturation Of Somatimentioning
confidence: 99%